Experimental infection with Trypanosoma evansi in rams: presence of parasite in semen, investigation of sexual transmission, hematological, and biochemical alterations. (July 2016) - Silva, Aleksandro; Campigotto, Gabriela; Sczesny, Tais; Pazinato, Rafael; Albani, Kassio; Klauck, Vanderlei; Grosskopf, Rhayana; Topazio, Josué; Galli, Gabriela; Cazzarotto, Chrystian; Ferreira, Rogério; Tonin, Alexandre; et al.
Abstract The aims of this study were to investigateTrypanosoma evansi venereal transmission in ewes and its presence in ram's semen and hematological and biochemical alterations. Three adult rams and six ewes were used as follows: one uninfected ram was used as control (R1), and two rams (R2 and R3) were intravenously infected byT. evansi trypomastigotes. Semen samples were collected weekly for PCR analyses that have detected the presence ofT. evansi . Blood samples were collected, and it was observed that the number of red blood cells and hemoglobin concentration were reduced in infected rams on day 14 post-infection (PI) toT. evansi when compared to uninfected ram. Likewise, the number of total leukocytes increased in infected rams, due to the increase of lymphocytes and monocytes. The values of total protein and globulin increased from day 14 PI in animals infected byT. evansi, but albumin levels were reduced for these animals on the same period. Testosterone levels on days 21, 28, and 35 PI were lower in rams infected byT. evansi . All rams served two ewes each 17 days PI. All ewes had synchronized estrus and 45 days after service gestational diagnosis was performed by ultrasound, confirming that all the ewes were pregnant. Blood samples from all ewes were collected every 30 days for 5 months for serological assays and PCR. All results from ewes were negative.T. evansi was detected in semen samples; there was no parasitic venereal transmission to ewes and no fertility impairment.